Creating firm value, overcoming organizational inertia through the marketing value chain - Palomino-Tamayo, Walter; Timaná, Juan S. (Emerald, 2022)
Purpose: Technology may produce disruptive changes and market turbulence in any industry. Organizational inertia becomes relevant as a factor that adversely affects organizational transformation; this study aims to examine how to overcome it and its consequences to firms. Design/methodology/approach: The model estimation with seemingly unrelated regression and two-stage least square. The authors build a data set of years 2015–2019 from the Lima Stock Exchange firms to test the hypotheses. Findings: In this research, using the evolutionary-ecological theory of Hannan and Freeman, the study shows the consequences of organizational inertia on marketing intensity and subsequently on firms' financial results. Originality/value: This study presents an inter-functional model that links organizational behavior, marketing and finance functions, through the marketing value chain to overcome organizational inertia and create firm value.

Propósito: La tecnología puede producir cambios disruptivos y turbulencias en el mercado en cualquier industria. La inercia organizacional cobra relevancia como factor que incide negativamente en la transformación organizacional; esta investigación examina cómo superarlo y sus consecuencias para las empresas. Diseño/metodología/enfoque: La estimación del modelo es con regresión aparentemente no relacionada (SUR) y mínimos cuadrados de dos etapas (2SLS). Para probar las hipótesis, los autores construyen un conjunto de datos de los años 2015–2019 de firmas de la bolsa de valores de Lima. Resultados: En esta investigación, utilizando la teoría ecológica evolutiva de Hannan y Freeman, el estudio muestra las consecuencias de la inercia organizacional en la intensidad del marketing y, posteriormente, en los resultados financieros de las empresas. Originalidad/valor: Este estudio presenta un modelo interfuncional que vincula el comportamiento organizacional, las funciones de marketing y finanzas, a través de la cadena de valor del marketing para superar la inercia organizacional y crear valor para la empresa.
Keywords: Firm value; Firm performance; Organizational inertia; Marketing intensity; Marketing value chain; Valor de la empresa; Desempeño de la empresa; Inercia organizacional; Intensidad del marketing; Cadena de valor del marketing; https://purl.org/pe-repo/ocde/ford#5.02.04